Pengaruh Model Pembelajaran Value Clarification Technique (VCT) Terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Agama Islam dan Budi Pekerti - Martin Kustati; Nurul Hidayah Siregar; Rezki Amelia (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This research is driven by the notion that the current learning process predominantly privileges the instructor, resulting in insufficient student engagement. Islamic Religious Education and Ethics educators continue to use traditional instructional methods. The instructional approach employed lacks the ability to actively involve students. The aim of this study was to conduct a comprehensive analysis of the learning outcomes in the experimental and control courses of Islamic Religious Education and Budi Pekerti for eleventh-grade students at SMA Negeri 9 Padang, both before and after the examinations. Furthermore, the study aimed to evaluate the impact of the Value Clarification Technique (VCT) instructional style on student academic performance in particular courses and grade levels at SMA Negeri 9 Padang. The findings indicated that the average first learning outcomes for the experimental group were 47.78, while for the control group it was 55.68. Furthermore, the experimental group exhibited an average post-test score of 82.42 for PAI learning outcomes, whereas the control group achieved an average post-test score of 79.25. The t-test analysis performed using SPSS version 26 yielded a two-sided significance α (2-tailed) of 0.000, indicating that the observed outcome is statistically significant (0.000 < 0.05). This implies that the null hypothesis (Ho) is rejected, indicating that there are differences in educational results between Islamic Religious Education and Budi Pekerti while using the Value Clarification Technique (VCT) learning approach in Class XI IPA SMA Negeri 9 Padang.